DESIGN AND TESTING OF A TEST SPECIMEN TO MEASURE THE NATURAL FREQUENCY USING SOUND MEASUREMENT AS THE REPLACEMENT FOR VIBRATION MEASUREMENT - Nada Shafa Widintya, Nisrina
Frequency Response Function (FRF) testing using vibration measurement can be used to detect the looseness or cracking in steam turbine blades based on its natural frequency. However, the existing testing method using vibration measurement is time-consuming which lead to the need of an alternative method that overcomes this problem. One of the alternative methods that might be used is sound measurement. However, before the FRF testing of sound measurement can be carried out, the test requires a specimen that can simulate several blades that is attached to the base. Hence, this work aims to design, manufacture, and test this specimen to investigate the possibility of using sound measurement as the replacement of vibration measurement to measure the natural frequency of turbine blades. This research began with a development of design requirements as the DR&O, which is then proceeded by designing the test specimen. The specimen is constructed using five test beams and one base. The test specimen was then manufactured using cutting and welding processes. Once constructed, the natural frequency of the test specimen was measured by using both sound and vibration measurements. The results obtained from the sound measurement are then compared with the results of vibration measurement. In this research, the specimen has been made in accordance to the DR&O criteria and used in the experiment. Based on the experiment it can be conducted that the value of natural frequency from the results of sound measurement has a similar value as the vibration measurement. The maximum differences between these two types of measurements is 0.1 Hz. This difference is not significant because the frequency resolution of the experiment is 0.1 Hz. Therefore, the results of the experiment obtained are the value rounded to the nearest 0.1 Hz.